Mechanism of Inflammatory Associated Impairment of Sperm Function, Spermatogenesis and Steroidogenesis - Hasan, Hiba; Bhushan, Sudhanshu; Fijak, Monika; Meinhardt, Andreas (Frontiers in Endocrinology, 2022)
Infection and inflammation are relevant entities of male reproductive disorders that can lead to sub-/infertility. Associated damage of the testis of affected men and in rodent models include leukocytic infiltration, edema formation, fibrosis, germ cell loss and reduced androgen levels. Negative effects on spermatogenesis are thought to be elicited by oxidative stress sustained mostly by increased levels of ROS and pro-inflammatory cytokines. Under normal conditions these cytokines have physiological functions. However, increased levels as seen in inflammation and infection, but also in obesity and cancer are harmful for germ cells and impair steroidogenesis. As a summary, there is mounting evidence that the activation of inflammatory pathways is a rather common feature in various forms of male testicular disorders that extends beyond established infectious/inflammatory cues. This mini review will focus on relevant entities and the mechanisms of how a dysbalance of local testicular factors contributes to disturbances of spermatogenesis and steroidogenesis.